Mefenamic Acid Induced Nephrotoxicity: An Animal Model - Muhammad Nazrul Somchit; Faizah Sanat; Gan Eng Hui; Shahrin Iskandar Wahab; Zuraini Ahmad (Tabriz University of Medical Sciences, 2014)
Purpose: Nonsteroidal anti-inflammatory drugs (NSAIDs) are used for the treatment of many joint disorders, inflammation and to control pain. Numerous reports have indicated that NSAIDs are capable of producing nephrotoxicity in human. Therefore, the objective of this study was to evaluate mefenamic acid, a NSAID nephrotoxicity in an animal model. Methods: Mice were dosed intraperitoneally with mefenamic acid either as a single dose (100 or 200 mg/kg in 10% Dimethyl sulfoxide/Palm oil) or as single daily doses for 14 days (50 or 100 mg/kg in 10% Dimethyl sulfoxide/Palm oil per day). Venous blood samples from mice during the dosing period were taken prior to and 14 days post-dosing from cardiac puncture into heparinized vials. Plasma blood urea nitrogen (BUN) and creatinine activities were measured. Results: Single dose of mefenamic acid induced mild alteration of kidney histology mainly mild glomerular necrosis and tubular atrophy. Interestingly, chronic doses induced a dose dependent glomerular necrosis, massive degeneration, inflammation and tubular atrophy. Plasma blood urea nitrogen was statistically elevated in mice treated with mefenamic acid for 14 days similar to plasma creatinine. Conclusion: Results from this study suggest that mefenamic acid as with other NSAIDs capable of producing nephrotoxicity. Therefore, the study of the exact mechanism of mefenamic acid induced severe nephrotoxicity can be done in this animal model.